Drug prescriptions in elderly hospitalized patients with cognitive impairment in the Italian Dementia Friendly Hospital project - Govoni, Stefano; Rosi, Alessia; Preda, Stefania; Lanni, Cristina; Cappa, Stefano; Allegri, Nicola (Frontiers in Pharmacology, 2024)
Objective: The aim was to characterize drug prescription patterns in elderly patients hospitalized in acute wards as a function of cognitive status and staff training. Methods: We recorded clinical parameters reflecting health status and drug prescriptions at admission, during hospital stay and at discharge before and after a short staff training on the needs of aged cognitively impaired patients. Participants aged 65 and older had a Mini-Mental State Examination (MMSE) score > 16. The number of prescriptions, sedative and anticholinergic load, and drug–drug interactions were evaluated. 116 older patients were analysed; 59 patients were cognitively impaired and 57 were cognitively normal with a MMSE value >24; 59 patients were assisted by the hospital health staff after training. Results: Participants presented a widespread polypharmacy. Cognitively impaired patients received more prescriptions, more inappropriate prescriptions, had a greater sedative load and were exposed to more interactions. The training of the staff had no effect on the prescription pattern. Conclusions: The results suggest that hospitalized cognitively impaired patients are overprescribed psychotropic drugs and have an excessive sedative and anticholinergic load. Intervention on improving dementia care practices in health staff, but not designed to manage drug polypharmacy, do not modify prescription patterns.